Targeting focal ischemic and hemorrhagic stroke neuroprotection: Current prospects for local hypothermia. Issue 1 (21st September 2021) - Liddle, Lane J.; Kalisvaart, Anna C. J.; Abrahart, Ashley H.; Almekhlafi, Mohammed; Demchuk, Andrew; Colbourne, Frederick
Abstract: Therapeutic hypothermia (TH) has applications dating back millennia. In modern history, however, TH saw its importation into medical practice where investigations have demonstrated that TH is efficacious in ischemic insults, notably cardiac arrest and hypoxic‐ischemic encephalopathy. As well, studies have been undertaken to investigate whether TH can provide benefit in focal stroke (i.e., focal ischemia and intracerebral hemorrhage). However, clinical studies have encountered various challenges with induction and maintenance of post‐stroke TH. Most clinical studies have attempted to use body‐wide cooling protocols, commonly hindered by side effects that can worsen post‐stroke outcomes. Some of the complications and difficulties with systemic TH can be circumvented by using local hypothermia (LH) methods. Additional advantages include the potential for lower target temperatures to be achieved and faster TH induction rates with LH. This systematic review summarizes the body of clinical and preclinical LH focal stroke studies and raises key points to consider for future LH research. We conclude with an overview of LH neuroprotective mechanisms and a comparison of LH mechanisms with those observed with systemic TH. Overall, whereas many LH studies have been conducted preclinically in the context of focal ischemia, insufficient work has been done in intracerebral hemorrhage. Furthermore, key translational studies have yet to be done in either stroke subtype (e.g., varied models and time‐to‐treat, studies considering aged animals or animals with co‐morbidities). Few clinical LH investigations have been performed and the optimal LH parameters to achieve neuroprotection are unknown. Abstract : Local hypothermia is a promising treatment for focal stroke that cools the injured regions of the brain, avoiding many complications associated with whole body cooling. Despite its promise, there has been limited investigation into how to best optimize neuroprotective efficacy of local cooling, with studies often assessing a single set of treatment parameters and limited mechanistic targets, and in homogenous models. To improve the odds for future clinical translation, a deeper mechanistic understanding of how to best optimize hypothermic neuroprotection in each treatment paradigm is needed, and the impact of varying treatment parameters must be understood while still considering clinical relevance.